Adapting oil and gas downhole motors for deep mineral exploration drilling - Mokaramian, Amir; Rasouli, Vamegh; Cavanough, G. (Australian Centre for Geomechanics, 2012)
Drilling deep boreholes for exploration of some mineral deposits are becoming more popular in many areas. This is while drilling very deep wells is very common in oil and gas industry with the objective of production from hydrocarbon reservoirs. Therefore, it is a sensible practice to initiate the idea of transferring the technologies currently in use in oil and gas industry to the mining operations. In particular, in deep drilling delivering the required power directly to the bit and independent of rotating the drillstring has attracted huge attentions for several technical and economic reasons. This is done using downhole motors which are mounted right before the drill bit. The initial design and usage of downhole motors for applications in oil and gas industry goes back to 1924. Since then extensive advancements have been made in the design of downhole motors which has resulted to some new generations of high speed mud motors resulting in a power output of around 735 KW. These motors can function in temperatures of higher than 160°C and have survived numerous runs consisting of hundreds of hours of on-bottom drilling time without failure. Further developments in the design of new motors which serve particular operating conditions are in progress. Considering that mining drilling is a different environment than that of drilling for oil and gas purposes, adapting downhole motors developed for the latter applications require different modifications to serve the requirements for deep mining drilling.In this paper, a review of downhole motors which are used in both petroleum and mining industries is presented. Technical design parameters for different type of downhole motors is listed and discussed in detail. This will enable us to identify the areas where modifications are required for the downhole motors to serve the functions expected for deep mineral exploration drilling. Drilling fluid specifications and environmental impact are some of the parameters to be compared between a typical mining and oil and gas drilling. This study which is part of the deep exploration technologies cooperative research centre (DET CRC) program concluded possible adaption of downhole motors for mineral exploration drilling and provides the range of modifications required for this purpose to the current downhole motors used in the oil and gas industry.